Neuroanatomy of titanosaurid dinosaurs from the Upper Cretaceous of Patagonia, with comments on endocranial varibility within Sauropoda - Paulina Carabajal, Ariana (The Anatomical Record: Advances in Integrative Anatomy and Evolutionary Biology)
The purpose of this study is to provide a detailed description of the neuroanatomy of Bonatitan, Antarctosaurus, and an unnamed titanosaur from Río Negro, Argentina including the first observations on the inner ear of the two first taxa using CT scans. The materials were compared with previously described sauropod endocasts and other less complete titanosaur braincases from Argentina. The cranial endocasts show the general morphology of other sauropods being bulbous, anteroposteriorly short and transversely wide, and with enlarged and posteroventrally projected pituitary body. Particular titanosaur traits are the extremely short and horizontal olfactory tract, the absence of a floccular process and a single root for cranial nerve XII. In addition, in the basicranium the abducens nerve (CN VI) does not penetrates the pituitary fossa and the internal carotid artery enters the medial aspect of the basipterygoid process, resulting in an external opening for this vessel that is not visible in lateral view of the braincase. The titanosaurid inner ear also exhibits particular traits, such as robust semicircular canals, and anterior and posterior semicircular canals that are subequal in size. The variation observed in the sauropod endocranium indicates an evolutionary tendency in titanosaurs toward the anteroposterior shortening of the midbrain, and the reduction in size of the semicircular canals of the inner ear, in particular the anterior semicircular canal. This, together with the lack of floccular process suggests a narrower range of movements of the head for this clade. Fil: Paulina Carabajal, Ariana. Provincia del Neuquén. Municipalidad de Plaza Huincul. Museo "Carmen Funes"; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Confluencia; Argentina